Frequency of Cognitive Impairment in Multiple Sclerosis: Association with Neuro-Imaging Parameters and Disease Duration : Cognitive Impairment in Multiple Sclerosis: Association with Neuro-Imaging Parameters - Shehzad, Amna; Gul, Qamar; Ashraf, Muhammad Salman; Naeem, Iqra; Zaheer, Mohsin; Ather, Faiza (Pakistan Journal of Health Sciences, 2026)
Cognitive impairment is a frequent but underrecognized feature of multiple sclerosis and contributes to functional decline. Early identification and association with clinical and neuroimaging markers may guide management. Objectives: To determine the frequency of cognitive impairment and its relationship with demographic, clinical, and MRI characteristics in multiple sclerosis. Methods: This cross-sectional study was conducted at the Department of Neurology, Punjab Institute of Neurosciences, Lahore, from May to December 2025. Seventy-one adults aged 18–50 years with multiple sclerosis, diagnosed according to the 2017 Revised McDonald Criteria, were enrolled. Brain MRI on a 3-Tesla system was evaluated for lesion characteristics and atrophy by a radiologist. Cognitive function was assessed using the Montreal Cognitive Assessment. Results: The mean age of participants was 35.08 ± 7.71 years, and the mean disease duration was 6.53 ± 3.24 years. The mean Montreal Cognitive Assessment (MoCA) score was 22.91 ± 5.87, and the mean total MRI lesion count was 16.07 ± 8.98. Cognitive impairment was found in 40.8%, including 21.,1% mild, 12.7% moderate, and 7.0% severe impairment. Relapsing–remitting multiple sclerosis was most common (69.0%), followed by secondary progressive (19.7%) and primary progressive (11.3%). Patients with impairment had older age (p=0.016) and longer disease duration (p=0.012). Cortical lesions and brain atrophy were significantly related to cognitive impairment. Conclusions: Cognitive impairment appeared as a frequent feature of multiple sclerosis and was related to advancing age, longer disease duration, and neuroimaging abnormalities.